Substituição de farinha de peixe por farelo de soja para juvenis de pacamã (Lophiosilurus alexandri) - Deborah Rodrigues Pedrosa Soares (2014)
This study aimed to evaluate biochemical and performance parameters of juvenile pacamã (Lophiosilurus alexandri), subjected to diets formulated with different replacement levels of fishmeal by soybean meal, as a protein source in the feed. Thereunto, weight gain, consumption, protein efficiency, size of intestinal villus, hepatossomatic rate, chemical body composition, total plasmatic protein, glycemia, haematocrit, doses of alanine aminotranferase and aspartate aminotranferase were analyzed. The animals were separated into three categories (S, M and L), according to their weight. Each category was composed by two repetitions per treatment. Five diets (0, 25, 50, 75 and 100% of soybean inclusion in replacement of fishmeal) and six repetitions were tested, totalizing 30 parcels. The experiment lasted 74 days, being five of adaptation and 69 of the experimental diets supply. The food was provided three times a day, at 8a.m., 12p.m. and 4p.m. The experimental test was performed in a recirculation water laboratory, using 30 boxes of fiberglass, with total capacity of 100L each. The temperature was monitored daily, twice a day, at 8a.m. and 4p.m. The monitoring of pH and oxygen was done weekly. The data obtained were analyzed using the INFOSTAT software. The averages were compared by the Tukey probability test, at 5% of significance when parametric, and by the Kruskal-Wallis test, also at 5% of significance, when not parametric. The temperature remained stable during the entire experimental period, presenting an average value of 28.93±0.36°C. The same happened with the amounts of pH and dissolved oxygen, which showed average values of 7.40±0.14 and 6.13±0.50 mg/L respectively. The survival rate was 100% for all treatments. The consumption, weight gain (daily and average), and hepatossomatic rate averages showed a statistic difference between categories, the protein efficiency, size of intestinal villus, and total weight gain, however, showed no difference between the treatments and tested categories. The analyze of animal carcasses also showed statistic difference between categories for mineral matter, crude protein, dry matter and ethereal extract, with the last one also being statistically different between treatments. Among the blood parameters analyzed (glucose, haematocrit, total protein, enzymes AST and ALT) only haematocrit did not show a significant difference between categories. Total plasmatic protein was different between categories and treatments, Even though some livestock indexes showed statistic difference, it is possible to conclude that fishmeal can be fully replaced by soybean meal for juvenile pacamã (Lophiosilurus alexandri), with no injury to the animal physiology and consequently to the breeding, within a period of 69 days.